What Prevents Quality Midwifery Care? A Systematic Mapping of Barriers in Low and Middle Income Countries from the Provider Perspective. - Alex Filby; Fran McConville; Anayda Portela (PLoS ONE)
Background Quality of care is essential for further progress in reducing maternal and newborn deaths. The integration of educated, trained, regulated and licensed midwives into the health system is associated with improved quality of care and sustained decreases in maternal and newborn mortality. To date, research on barriers to quality of care for women and newborns has not given due attention to the care provider's perspective. This paper addresses this gap by presenting the findings of a systematic mapping of the literature of the social, economic and professional barriers preventing midwifery personnel in low and middle income countries (LMICs) from providing quality of care. Methods and findings A systematic search of five electronic databases for literature published between January 1990 and August 2013. Eligible items included published and unpublished items in all languages. Items were screened against inclusion and exclusion criteria, yielding 82 items from 34 countries. 44% discussed countries or regions in Africa, 38% in Asia, and 5% in the Americas. Nearly half the articles were published since 2011. Data was extracted and presented in a narrative synthesis and tables. Items were organized into three categories; social; economic and professional barriers, based on an analytical framework. Barriers connected to the socially and culturally constructed context of childbirth, although least reported, appear instrumental in preventing quality midwifery care. Conclusions Significant social and cultural, economic and professional barriers can prevent the provision of quality midwifery care in LMICs. An analytical framework is proposed to show how the overlaps between the barriers reinforce each other, and that they arise from gender inequality. Links are made between burn out and moral distress, caused by the barriers, and poor quality care. Ongoing mechanisms to improve quality care will need to address the barriers from the midwifery provider perspective, as well as the underlying gender inequality.